2020
DOI: 10.1038/s41467-020-19106-z
|View full text |Cite
|
Sign up to set email alerts
|

Lithium systematics in global arc magmas and the importance of crustal thickening for lithium enrichment

Abstract: Much of the world’s Li deposits occurs as basinal brines in magmatic orogens, particularly in continental volcanic arcs. However, the exact origin of Li enrichment in arc magmatic systems is not clear. Here, we show that, globally, primitive arc magmas have Li contents and Li/Y ratios similar to mid-ocean ridge basalts, indicating that the subducting slab has limited contribution to Li enrichment in arc magmas. Instead, we find that Li enrichment is enhanced by lower degrees of sub-arc mantle melting and highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 57 publications
0
26
0
2
Order By: Relevance
“…Such a tectonic scenario is consistent with our results that arc crust in the upper Yili-Central Tianshan plate was less than ∼30 km (Figure S3 in Supporting Information S1) in the Late Carboniferous (e.g., 306 Ma U-Pb age of the syenite). This may be a favorable condition to produce intermediate melts because thick crusts will suppress mantle wedge melting and enhance intra-crustal differentiation, corresponding to statistical results that the SiO 2 content for arcs of crustal thicknesses less than 50 km is mafic-intermediate (48-60 wt.% SiO 2 ; Figure S3 in Supporting Information S1; Chen et al, 2020). Furthermore, a low oxygen fugacity of alkaline arc magmas (ΔFMQ < 0; Figure S3 in Supporting Information S1) also supports our speculation because thick crusts particularly enhance the differentiation of garnets (absorb much Fe 2+ ), which will result in high oxygen fugacity in melts (Tang et al, 2020).…”
Section: Geodynamic Setting Relevant To Mélange Diapirmentioning
confidence: 72%
“…Such a tectonic scenario is consistent with our results that arc crust in the upper Yili-Central Tianshan plate was less than ∼30 km (Figure S3 in Supporting Information S1) in the Late Carboniferous (e.g., 306 Ma U-Pb age of the syenite). This may be a favorable condition to produce intermediate melts because thick crusts will suppress mantle wedge melting and enhance intra-crustal differentiation, corresponding to statistical results that the SiO 2 content for arcs of crustal thicknesses less than 50 km is mafic-intermediate (48-60 wt.% SiO 2 ; Figure S3 in Supporting Information S1; Chen et al, 2020). Furthermore, a low oxygen fugacity of alkaline arc magmas (ΔFMQ < 0; Figure S3 in Supporting Information S1) also supports our speculation because thick crusts particularly enhance the differentiation of garnets (absorb much Fe 2+ ), which will result in high oxygen fugacity in melts (Tang et al, 2020).…”
Section: Geodynamic Setting Relevant To Mélange Diapirmentioning
confidence: 72%
“…Next to these times of quiescence, compositional trends are observed that may be related to either general trends of New Zealand’s subduction systems, changes between the arc systems with time, or contribution from other volcanic sources. Tentative interpretations can be made on the base of the variations within trace element ratios regarding increasing or decreasing fluid and/or crustal contamination/interaction or variable melting degree (e.g., crust: Chen et al., 2020; Walker et al., 2007; Waight et al., 2017; fluids: Bolge et al., 2009; Carr et al., 1990; Elliott, 2003; Plank, 2014; Zamboni et al., 2016; melting degree: Münker, 2000; Pfänder et al., 2012; Zirakparvar, 2016). Starting in the early Late Miocene (11 Ma) until the second and most pronounced gap in our tephra record, two (Figure 7c) to three (Figure 7e) distinct compositions can be identified within the tephra time series possibly indicating a different volcanic source for the related tephras associated with higher fluid (Figure 7c) and lower crustal (Figures 7e and 7f) interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Next to these times of quiescence, compositional trends are observed that may be related to either general trends of New Zealand's subduction systems, changes between the arc systems with time, or contribution from other volcanic sources. Tentative interpretations can be made on the base of the variations within trace element ratios regarding increasing or decreasing fluid and/or crustal contamination/interaction or variable melting degree (e.g., crust: Chen et al, 2020;Walker et al, 2007;Waight et al, 2017;fluids: Bolge et al, 2009;Carr et al, 1990;Elliott, 2003;Plank, 2014;Zamboni et al, 2016;melting degree: Münker, 2000;Pfänder et al, 2012;Zirakparvar, 2016).…”
Section: Geochemical Evolution From Cvz To Tvz Volcanismmentioning
confidence: 99%
“…However, geothermal and/or volcanic associations are the other mechanisms introducing Li into continental basins (Eccles and Berhane, 2011;Kesler et al 2012;Benson et al 2017). Much of the world's Li occurs as basinal brines in magmatic units, particularly in continental volcanic arcs (Chen et al 2020). Past studies have also shown that B and Li released from organic macerals during thermal maturation (Teichert et al 2020;Williams and Hervig 2005;Williams et al 2013) can lead to enrichment of elemental B and Li in oilfield water with lower δ 11 B and δ 7 Li relative to the expected chemical and isotopic trajectory of evaporated seawater (Macpherson 2015;Macpherson et al 2014;Ni et al 2018;Pfister et al 2017;Phan et al 2020;Warner et al 2014;Williams et al 2001Williams et al , 2015.…”
Section: Application Of LI Isotopes In Deep Groundwater Studiesmentioning
confidence: 99%